Pengaruh Model Pembelajaran Group Investigation (GI) Terhadap Hasil Belajar Biologi Pada Materi Ekosistem - Diana, Diana; Anisa, Anisa (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research is a pre-experimental research which aims to determine the effect of using the Goup Investigation (GI) model on the learning outcomes of class X MAs Darunnajah Botong students on ecosystem material with a